No independent role of the -1123 G>C and+2740 A>G variants in the association of PTPN22 with type 1 diabetes and juvenile idiopathic arthritis in two Caucasian populations - Cinek, Ondrej; Hradsky, Ondrej; Ahmedov, Gunduz; Slavcev, Antonij; Kolouskova, Stanislava; Kulich, Michal; Sumnik, Zdenek (Diabetes research and clinical practice, 2007)
INTRODUCTION: The PTPN22 is a negative regulator of the T cell response. Its +1858C>T (R620W) polymorphism has been shown to associate with a risk for multiple autoimmune diseases, including type 1 diabetes (T1D) and juvenile idiopathic arthritis (JIA). The minor (susceptibility) allele is absent in Asian populations, but a recent study suggested an independent involvement of another polymorphism located within the promoter -1123 nucleotides relative to the translational start site. AIMS: We aimed to analyse the association of three PTPN22 polymorphisms in two distinct Caucasian populations, the Czechs (with T1D and with JIA) and Azeri (with T1D). METHODS: The single nucleotide polymorphisms (SNP) at positions -1123 (rs2488457), +1858 (rs2476601, the R620W substitution), and +2740 (rs1217412) were genotyped using TaqMan assays in 372 subjects with childhood-onset T1D, 130 subjects with JIA, and 400 control subjects of Czech origin, and in 160 subjects with T1D and 271 healthy controls of Azeri origin. RESULTS: In the Czechs, all three SNPs were in a tight linkage disequlibrium, while in the Azeri, the linkage disequlibrium was limited to between the promoter and 3'-UTR polymorphism, D'(-1123, +2740)=0.99, r(2)=0.72. Haplotype reconstruction via the expectation-maximization algorithm showed in both populations that only the haplotype containing the minor (W) allele at codon 620 was associated with T1D (OR=2.26, 95% CI 1.68-3.02 in Czechs, OR=14.8, 95% CI 2.0-651 in Azeri) or JIA (OR=2.43, 95% CI 1.66-3.56 in Czechs). The haplotypes having the wild-type (R) allele at codon 620 and minor alleles at -1123 and/or +2740 were neutral as to the risk of autoimmune conditions in both populations. CONCLUSIONS: In two different Caucasian populations, the Czechs and the Azeri, no independent contribution can be detected either of the -1123 promoter SNP or the +2740 3'-UTR SNP, and only the minor allele at PTPN22 codon 620 contributes to the risk of autoimmunity.
Keywords: dospělí; Genotype; Female; dítě; Adult; ženské pohlaví; jednonukleotidový polymorfismus; Adolescent; Gene Frequency; lidé; Polymorphism, Single Nucleotide; genotyp; Protein Tyrosine Phosphatase, Non-Receptor Type 22; genetická predispozice k nemoci; studie případů a kontrol; Linkage Disequilibrium; Genetic Predisposition to Disease; vazebná nerovnováha; frekvence genu; Humans; tyrosinfosfatasy; Diabetes Mellitus, Type 1; Protein Tyrosine Phosphatases; Male; Case-Control Studies; Haplotypes; alely; Alleles; Child; juvenilní artritida; haplotypy; mužské pohlaví; Arthritis, Juvenile; Protein Tyrosine Phosphatase, Non-Receptor Type 1; White People; tyrosinfosfatasa nereceptorového typu 22; běloši; mladiství; diabetes mellitus 1. typu; tyrosinfosfatasa nereceptorového typu 1